An assistance in optimizing the liquid organic fertilizer to increase sustainable agricultural yields in Jorong Arikia, Nagari Dalko Kabupaten Agam, West Sumatra - Z, Martias; Muttaqiin, Arief; Suryani, Okta; Amelia, Kiki (Fakultas MIPA Universitas Negeri Padang, 2025)
Organic fertilizers have been popular lately because they are believed to increase agricultural yields and are environmentally friendly. With the increasing popularity of fertilizer use, farmers have innovated to make their organic fertilizers using materials available in their surroundings. The problem experienced by farmers is regarding the testing of the fertilizer produced. This community service activity aims to assist farmers in testing fertilizers in the laboratory and provide insight into testing the effectiveness of fertilizers in Jorong Arikia, Nagari Dalko, Agam Regency, aided by 39 students from Padang State University. Assistance is carried out through discussions related to fertilizers, then continued with preparing for testing and assisting in testing fertilizers. The results of this community service activity are increasing farmers' insight in testing organic fertilizers so that the fertilizers produced can optimize harvest results, be certified, and be produced on a large scale to encourage economic growth in the region. In addition, this PkM activity also aims to provide a forum for UNP students who are carrying out community service program activities to be able to practice the knowledge they have gained on campus in the field. Thus, this PkM program is directly integrated with campus activities and is expected to develop further in the future so as to provide a greater contribution to society.